Neocortical neurogenesis is not really "neo": A new evolutionary model derived from a comparative study of chick pallial development. (12th December 2012) - Suzuki, Ikuo K.; Hirata, Tatsumi
<x xml:space="preserve">Abstract</x> The neocortex facilitates mammalian adaptive radiation by conferring highly sophisticated cognitive and motor abilities. A unique feature of the mammalian neocortex is its laminar structure in which similar neuronal subtypes are arranged in tangential layers and construct columnar circuits via interlaminar connections. The neocortical layer structure is completely conserved among all mammalian species, including monotremes and marsupials. However, this structure is missing in non‐mammalian sister groups, such as birds and reptiles. The evolutionary origins of neocortical layers and cytoarchitectural borders have been the subject of debate over the past century. Using the chicken embryos as a model of evolutionary developmental biology (evo‐devo model), we recently provided evidence suggesting that the evolutionary origin of layer‐specific neuron subtypes predates the emergence of laminar structures. Based on this finding, we review the evolutionary conservation and divergence of neocortical development between mammals and non‐mammals and discuss how the layered cytoarchitecture of the mammalian neocortex originated during evolution.